Efficacy, safety and cost effectiveness of oral doxofylline and theophylline for mild to moderate persistent bronchial asthma: A randomized prospective open labeled comparative study - NANDHINI PRIYA.M; PURUSHOTHAMAN.S (International Journal of Pharma and Bio Sciences, 2018)
A Randomized Prospective open labelled comparative study was conducted in the thoracic medicine outpatient department of tertiary care centre to compare the efficacy, safety and cost effectiveness of oral Doxofylline and Theophylline for mild to moderate persistent bronchial asthma patients. The study subjects were randomly allocated into two groups. Group 1 patients were treated with Doxofylline 400mg once daily and group 2 patients were treated with Theophylline 200mg twice daily. Demographic data, history, clinical examination, details of drug prescription and relevant lab investigations were recorded in the study proforma. The patients were followed for 12 weeks. Doxofylline was better than theophylline in subjective parameters and it had equal efficacy as that of theophylline in objective parameters (p ≤ 0.001). Doxofylline was significantly safe compared to theophylline as inferred from lesser incidence of adverse drug reactions, 10% in doxofylline group and 22% in theophylline group. Theophylline was the cheaper and cost effective methylxanthine at population level. Doxofylline can be used as an individual based approach. It is a better alternative in the management of bronchial asthma.